Ghanshyam Das Birla - Visual History of Business and Trade in India (2022)
G.D. Birla was an outstanding architect of India's industrial growth. The founding father of the Birla empire, he also established the Federation of Indian Chambers of Commerce and Industry (FICCI). He migrated to Calcutta at the age of 16 and started a career as a jute broker along with his brothers. It wasn't long before his hard work paid rich dividends and in 1919 he set up Birla Brothers Limited and thereafter a mill in Gwalior. He established a cotton mill in Sabzi Mandi, Delhi followed by Keshoram Cotton Mills and Birla Jute Mills around 1920. By 1939, Birla Brothers were India's 13th largest managing-agency firm. The expansion was almost an unstoppable phenomenon with Ghanshyam Das and in the decade of the 1930s, he set up Sugar and Paper mills, and in the 1940s ventured into the automobiles, insurance, and air service industries. Post-Independence, he set up an aluminum plant 'Hindalco' near Mirzapur, and the coming decades continued to see the Birla Brothers among the top industrial houses of India.